2016
DOI: 10.1242/dev.132340
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT signalling mediates cell survival in response to tissue stress

Abstract: Tissue homeostasis relies on the ability of tissues to respond to stress. Tissue regeneration and tumour models in Drosophila have shown that c-Jun amino-terminal kinase (JNK) acts as a prominent stress-response pathway promoting injury-induced apoptosis and compensatory proliferation. A central question remaining unanswered is how both responses are balanced by activation of a single pathway. Signalling through the Janus kinase/Signal transducers and activators of transcription (JAK/STAT) pathway, which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 104 publications
(95 reference statements)
9
106
0
Order By: Relevance
“…Among the modulated pathways analyzed, we found Jak/Stat. This pathway has been shown to mediate different responses to various forms of biological stress, including hypoxia/reperfusion, endotoxin, ultraviolet light, and hyperosmolarity . Our results demonstrated pSTAT6 was highly active during starvation and was downregulated after the medium change, suggesting a direct relationship between its activation and the hyperosmotic and hypoxic conditions created during starvation.…”
Section: Discussionmentioning
confidence: 61%
“…Among the modulated pathways analyzed, we found Jak/Stat. This pathway has been shown to mediate different responses to various forms of biological stress, including hypoxia/reperfusion, endotoxin, ultraviolet light, and hyperosmolarity . Our results demonstrated pSTAT6 was highly active during starvation and was downregulated after the medium change, suggesting a direct relationship between its activation and the hyperosmotic and hypoxic conditions created during starvation.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies further showed that some signals including JAK/STAT and β‐catenin/TCF are required to facilitate the JNK‐dependent compensatory cell proliferation . The JNK component fos and the proapoptotic gene hid are regulated in a JAK/STAT‐dependent manner . The JAK/STAT pathway suppresses JNK signaling and restrains the JNK‐induced cell apoptosis.…”
Section: Mechanisms By Which Jnk Regulates Cancer Cell Survivalmentioning
confidence: 99%
“…Activation of JNK and p38 in surviving cells induces Upd ligands, particularly Upd3 (Ahmed- de-Prado et al, 2018;Katsuyama et al, 2015;Klebes et al, 2005;La Fortezza et al, 2016;Pastor-Pareja et al, 2008;Santabárbara-Ruiz et al, 2015;Worley et al, 2018). Notably, one study found that the same 4 kb upd3 enhancer induced in the Drosophila gut in response to damage was also induced in the wing disc during regeneration (Worley et al, 2018), indicating that Upd production in response to inflammation is a common feature in intestinal and appendage regeneration.…”
Section: Jak/stat Signaling In Regeneration Of the Drosophila Wing Discmentioning
confidence: 99%